A novel, stain-free, natural auto-fluorescent signal, Sig M, identified from cytometric and transcriptomic analysis of infectivity of Cryptosporidium hominis and Cryptosporidium parvum - Ogbuigwe, Paul; Roberts, Joanna M.; Knox, Matthew A.; Heiser, Axel; Pita, Anthony; Haack, Neville A.; Garcia-Ramirez, Juan Carlos; Velathanthiri, Niluka; Biggs, Patrick J.; French, Nigel P.; Hayman, David T. S. (Frontiers in Cellular and Infection Microbiology, 2023)
Cryptosporidiosis is a worldwide diarrheal disease caused by the protozoan Cryptosporidium. The primary symptom is diarrhea, but patients may exhibit different symptoms based on the species of the Cryptosporidium parasite they are infected with. Furthermore, some genotypes within species are more transmissible and apparently virulent than others. The mechanisms underpinning these differences are not understood, and an effective in vitro system for Cryptosporidium culture would help advance our understanding of these differences. Using COLO-680N cells, we employed flow cytometry and microscopy along with the C. parvum-specific antibody Sporo-Glo™ to characterize infected cells 48 h following an infection with C. parvum or C. hominis. The Cryptosporidium parvum-infected cells showed higher levels of signal using Sporo-Glo™ than C. hominis-infected cells, which was likely because Sporo-Glo™ was generated against C. parvum. We found a subset of cells from infected cultures that expressed a novel, dose-dependent auto-fluorescent signal that was detectable across a range of wavelengths. The population of cells that expressed this signal increased proportionately to the multiplicity of infection. The spectral cytometry results confirmed that the signature of this subset of host cells closely matched that of oocysts present in the infectious ecosystem, pointing to a parasitic origin. Present in both C. parvum and C. hominis cultures, we named this Sig M, and due to its distinct profile in cells from both infections, it could be a better marker for assessing Cryptosporidium infection in COLO-680N cells than Sporo-Glo™. We also noted Sig M’s impact on Sporo-Glo™ detection as Sporo-Glo™ uses fluoroscein–isothiocynate, which is detected where Sig M also fluoresces. Lastly, we used NanoString nCounter® analysis to investigate the transcriptomic landscape for the two Cryptosporidium species, assessing the gene expression of 144 host and parasite genes. Despite the host gene expression being at high levels, the levels of putative intracellular Cryptosporidium gene expression were low, with no significant difference from controls, which could be, in part, explained by the abundance of uninfected cells present as determined by both Sporo-Glo™ and Sig M analyses. This study shows for the first time that a natural auto-fluorescent signal, Sig M, linked to Cryptosporidium infection can be detected in infected host cells without any fluorescent labeling strategies and that the COLO-680N cell line and spectral cytometry could be useful tools to advance the understanding of Cryptosporidium infectivity.